SYSTEMATIC LITERATURE REVIEW OF SCIENTIFIC JOURNAL: TRANSLATIONSTECHNIQUE OF LITERARY TEXT OF POETRY - Samuel Jusuf Litualy; Eldaa Crystle Wenno; Henderika Serpara (JURNAL TAHURI, 2022)
Poetry is a unique literary work and is not easily translated from source language to target language because in the process, wherever possible maintain the inner atmosphere of the work (mood, tone). At the same time, translators should look for equivalents to the formal form of the poem itself appropriately, such as the number of lines (especially for sonnet type), rhyme (praying) and syllable (number of syllables). Therefore, it is necessary to review the journal paper that discusses the technique of translating the literary text of poetry. The method used by this study is Systematic Literature Review (SLR) on journal paper published from 2013-2021. There is one Research Question (RQ) set out in this study. The final result obtained from this study is that there are twenty-one techniques for translating poetry literary texts that can be used by translators according to the times, needs and objectives of translators